"What Would I Look Like?": How Exposure to Concentrated Disadvantage Shapes Hip-Hop Artists' Connections to Community. Issue 1 (January 2020) - Becker, Sarah; Sweet, Castel
Hip-hop has deep historical ties to disadvantaged communities. Resounding success in mainstream and global music markets potentially disrupts those connections. The authors use in-depth interviews with 25 self-defined rap/hip-hop artists to explore the significance of place in modern hip-hop. Bringing together historical studies of hip-hop and sociological neighborhood studies, the authors examine hip-hop artists' community connections. Findings reveal that exposure to concentrated racial and economic disadvantage shapes how artists interpret community, artistic impact, and social responsibility. This supports the "black placemaking" framework, which highlights how black urban neighborhood residents creatively build community amid structural disadvantage. The analysis also elucidates the role specific types of physical places play in black placemaking processes.